PENGARUH PEMBERIAN PUDING DAUN KELOR (MORINGA OLEIFERA) TERHADAP VOLUME ASI PADA IBU MENYUSUI DI PUKESMAS NILAM SARI KOTA BUKITTINGGI TAHUN 2024 - Nova H, Desri; Armi, Yeltra; Sari, Meka Melani; Afnas, Nur Hidayah (Ensiklopedia of Journal, 2025)
According to the World Health Organization (WHO), by 2025 the target is to increase the rate of exclusive breastfeeding by 50%. Based on the 2022 SDKI, the achievement of exclusive breastfeeding is 40%. Meanwhile, exclusive breastfeeding coverage meets the minimum target of 50%. The aim of this research was to determine the effect of giving moringa leaf pudding (moringa oleifera) on breast milk production in breastfeeding mothers at the nilam sari community health center in Bukittinggi City in 2024. The type of research used was quantitative with a quasi-experiment design with a one group pretest and posttest approach. The population in this study was all 48 breastfeeding mothers in the Patchouli Sari Health Center in Bukittinggi City in 2024, with a sample of 14 breastfeeding mothers. The intervention used in this research was giving Moringa leaf pudding to breastfeeding mothers and consuming it in one shot, given twice a day in the morning at 8 o'clock and in the afternoon at 5 o'clock for 7 days. The research results showed that the average volume of breast milk before the intervention given Moringa leaf pudding was 31.65 ml with a minimum of 28.4 and a maximum of 40.0. The average volume of breast milk after intervention was 51.22 ml with a minimum of 30.2 and a maximum of 71.4. The analysis used is univariate bivariate. The results of the Shapiro-Wilk normality test showed that (p=0.000), meaning that there was an effect of giving Moringa oleifera leaf pudding on the volume of breast milk in breastfeeding mothers. Suggestions for mothers to make Moringa leaf pudding an alternative way to improve breast milk production. Keywords: Moringa Leaf Pudding, Breast Milk Production, Breastfeeding Mothers